Cardiorespiratory Responses to an Acute Bout of High Intensity Interval Training and Moderate Intensity Continuous Training on a Recumbent Handcycle in People With Spinal Cord Injury: A Within-Subject Design. - Peters, Joseph; Halloran, Kellie; Focht, Michael; Huang, Kathryn; Kersh, Mariana; Rice, Ian (Topics in Spinal Cord Injury Rehabilitation)
To compare acute cardiorespiratory responses during high intensity interval training (HIIT) and moderate intensity continuous training (MICT) on a recumbent handcycle in persons with spinal cord injury (PwSCI). Eleven males and nine females with chronic SCI (T3 – L5), aged 23 (9) years, participated in this within-subject design. Based off peak power outputs from an incremental test to exhaustion, participants engaged in a HIIT and MICT session at matched workloads on a recumbent handcycle. Workloads (Joules), time, oxygen uptake (VO2), metabolic equivalent of task (MET), heart rate (HR), and energy expenditure (kcal) were recorded during HIIT and MICT. Total workload was similar across HIIT (87820 ± 24021 Joules) and MICT sessions (89044 ± 23696 Joules; p >.05). HIIT (20.00 [.03] minutes) was shorter in duration than MICT (23.20 [2.56]; p <.01). Average VO2 (20.96 ± 4.84 vs. 129.38 ± 19.13 mL/kg/min O2), MET (7.54 ± 2.00 vs. 6.21 ± 1.25), and HR (146.26 ± 13.80 vs. 129.38 ± 19.13 beats per minute) responses were significantly greater during HIIT than MICT (p <.01). Participants burned significantly more kilocalories during HIIT (128.08 ± 35.65) than MICT (118.93 ± 29.58; p <.01) and at a faster rate (6.40 ± 1.78 [HIIT] vs. 5.09 ± 1.14 [MICT] kcal/min; p <.01). HIIT elicits greater increases in oxygen uptake and HR than MICT in PwSCI. In significantly less time, HIIT also burned more calories than MICT.